2020
DOI: 10.1038/s41396-020-00776-y
|View full text |Cite
|
Sign up to set email alerts
|

Independent iron and light limitation in a low-light-adapted Prochlorococcus from the deep chlorophyll maximum

Abstract: Throughout the open ocean, a minimum in dissolved iron concentration (dFe) overlaps with the deep chlorophyll maximum (DCM), which marks the lower limit of the euphotic zone. Maximizing light capture in these dim waters is expected to require upregulation of Fe-bearing photosystems, further depleting dFe and possibly leading to co-limitation by both iron and light. However, this effect has not been quantified for important phytoplankton groups like Prochlorococcus, which contributes most of the productivity in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 20 publications
1
20
0
Order By: Relevance
“…Assuming a C:N ratio of 6.6, the corresponding Fe:C ratio, 8 μmol:mol, is below these Prochlorococcus Fe:C thresholds, suggesting that NO 3 ‐dependent growth in the cyclonic eddy would lead to Fe limitation. In contrast, some eukaryotic phytoplankton can grow at low irradiance with an Fe:C ratio below 5 μmol:mol (Maldonado & Price, 1996; Marchetti et al., 2006; Strzepek et al., 2012), likely because eukaryotic cells are able to support larger chlorophyll antennae than Prochlorococcus , decreasing the required number of photosynthetic reaction centers at low light (Bibby et al., 2003; Hawco et al., 2021; Strzepek et al., 2019). Lower photosynthetic Fe requirements among eukaryote phytoplankton could therefore allow NO 3 − drawdown without Fe limitation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Assuming a C:N ratio of 6.6, the corresponding Fe:C ratio, 8 μmol:mol, is below these Prochlorococcus Fe:C thresholds, suggesting that NO 3 ‐dependent growth in the cyclonic eddy would lead to Fe limitation. In contrast, some eukaryotic phytoplankton can grow at low irradiance with an Fe:C ratio below 5 μmol:mol (Maldonado & Price, 1996; Marchetti et al., 2006; Strzepek et al., 2012), likely because eukaryotic cells are able to support larger chlorophyll antennae than Prochlorococcus , decreasing the required number of photosynthetic reaction centers at low light (Bibby et al., 2003; Hawco et al., 2021; Strzepek et al., 2019). Lower photosynthetic Fe requirements among eukaryote phytoplankton could therefore allow NO 3 − drawdown without Fe limitation.…”
Section: Resultsmentioning
confidence: 99%
“…Relatively high iron requirements for Prochlorococcus photosynthesis may make them less competitive when NO 3 − supply increases. Experiments under DCM conditions with a low-light adapted Prochlorococcus (MIT1214 strain, LL1 ecotype) have indicated that the onset of Fe limitation is associated with an Fe:C ratio of 30-40 μmol:mol (Hawco et al, 2021), which is similar to the HLI Prochlorococcus strain MED4 when grown under low light (∼45 μmol:mol; Cunningham & John, 2017;Shire & Kustka, 2015). In the center of the cyclonic eddy, removal of 100 pM dFe was associated with the uptake of 2 μM NO 3 − .…”
Section: Prochlorococcus Fe Limitation In the Cyclonic Eddy?mentioning
confidence: 99%
“…Phytoplankton Fe-limitation at the DCM may emerge due to the upregulation of the Fe-rich photosynthetic apparatus under low light [59], which may increase Fe demand relative to supply [60] and thus low-light Prochlorococcus clades likely require more Fe than high-light clades [23]. Indeed, Prochlorococcus has relatively high photosynthetic Fe requirements under low irradiance, and there is evidence that LLI Prochlorococcus, in particular, is uniquely adapted to the low-Fe and low-light conditions typical of the DCM [23]. In some cases, the high Fe requirements of LLI Prochlorococcus may make them more sensitive to fluctuations in Fe concentration than eukaryotic phytoplankton [61].…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore Fe-limitation or Fe/light co-limitation is a persistent feature of this layer [22]. Phytoplankton Fe-limitation at the DCM may emerge due to the upregulation of the Fe-rich photosynthetic apparatus under low light [59], which may increase Fe demand relative to supply [60] and thus low-light Prochlorococcus clades likely require more Fe than high-light clades [23]. Indeed, Prochlorococcus has relatively high photosynthetic Fe requirements under low irradiance, and there is evidence that LLI Prochlorococcus, in particular, is uniquely adapted to the low-Fe and low-light conditions typical of the DCM [23].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation